Do the Size of Oil and Gas Firms Govern their Financial Performance? With Special Reference to Indian Oil and Gas Firms - Anis Ali; Nadeem Fatima (International Journal of Energy Economics and Policy, 2023)
The amount of profitability, liquidity, solvency, and resource utilization are used to evaluate a corporate organization's financial performance. The firm's size is determined by revenue, overall resources, and the availability of capital to execute the business operations. The study tries to get the governance of the financial performance by the size of firms in the Indian oil and gas sector.  The study is based on secondary data taken from the website of Indian oil and gas companies. ANOVA, stacked column chart, and Tukey’s homogeneity analysis applied for to get the disparity, variations and growth trend, and homogeneity of relative financial measures of financial performance. In Indian oil and gas firms, profitability is governed by the size of the firms negatively and directly while return on resources is negatively but negligibly by the size of the firms. There is no governance of liquidity and solvency by the size of firms in the Indian oil and gas industry. The larger manufacturing Indian oil and gas companies must increase their managerial and cost effectiveness in order to increase their profitability and absolute profits, while the smaller production Indian oil and gas companies must include debt in order to increase their level of activity and absolute profits.